Social Reality Stunting Prevention in Cianjur District - Willya Achmad (Jurnal EduHealth, 2022)
Social Reality is defined as a reality that forms an interaction pattern based on the values held by the community, stunting prevention is no longer talking about malnutrition but related to parenting patterns that affect stunting rates to go up or down. This study explains to find social reality in stunting prevention in the Cianjur Regency area, by using a literature study that is relevant to several events related to stunting problems in Indonesia, the results of this study explain that, malnutrition or poor nutrition and stunting or short stature ( stunting) is a global health problem, where the prevalence of these two health issues is still relatively high in developing countries, such as Indonesia and as one of the regions in Indonesia that contributes to the increased risk of stunting among children and toddlers, Cianjur Regency in fact still has a high prevalence of stunting. quite high, namely in the range of 37%. For this reason, the existence of a family companion team (TPK) is expected to be one of the efforts to accelerate the reduction of stunting in the Cianjur Regency area which has been established since 2020. The principles of stunting prevention are contained in the Cianjur regent regulation number 4 of 2020 concerning stunting prevention efforts. as well as the communication strategy for changing community behavior emphasizes that the community must be optimal and utilize existing resources and be mobilized to achieve optimal results, then act quickly and accurately, meaning that in efforts to prevent stunting, midwives, nutrition and trained health workers must act according to procedures. maintain nutrition services and professional code of ethics by prioritizing human aspects. Then strengthen inter-institutional and collaborative work, meaning that efforts to deal with stunting can not only be done sectorally, but require support from other sectors and programs that will be able to run optimally and effectively in the future.